Digital entrepreneurship and its role in brilliant performance an analytical : study of the opinions of a sample of senior leaders in the Baghdad Soft Drinks Company (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to know the digital leadership and its role in achieving the outstanding performance in the (Baghdad Soft Drinks) Company. In order to achieve the research goal, it was necessary to address the knowledge of digital leadership in achieving outstanding performance. The main research problem was formulated as the role of digital leadership in its dimensions in outstanding performance and its dimensions in the company. The research adopted the comparative analytical approach by targeting a deliberate sample of senior management levels (General Manager, Assistant General Manager, Head of Department, Division Manager, Unit Manager) as the size of the community reached (75) managers within the administrative specialties. The questionnaire form was distributed to a sample of (62) according to the "De" Morcan law to be the number of final forms valid for statistical analysis (54) respondents for the company, as the questionnaire is considered a main tool for research to collect information and data, in addition to adopting the checklist and personal interviews. The (Spss.v24) program was applied for the purpose of extracting the research results according to the selection of research hypotheses. The research showed a number of results, the most prominent of which was the presence of a significant effect Morale of digital leadership in outstanding performance. The senior management of Baghdad Soft Drinks Company also relied on using the latest methods in collecting and analyzing data, in addition to using technological technology in the decision-making stages as well as developing strategic plans.